Asylum policy in the West: past trends, future possibilities - Matthew J. Gibney; Randall Hansen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
This article examines the policy responses of Western countries in the realm of asylum. We begin by explaining the reasons why the asylum issue has made its way up the political agendas of liberal democratic countries in recent years. While applications for asylum have risen in the last two decades, we also highlight the way rights-based constraints and financial costs have contributed to controversy around the issue. We then examine in detail the major policy responses of states to asylum, grouping them into four main categories: measures aiming to prevent access to state territory, measures to deter arrivals, measures to limit stay, and measures to manage arrival. Moving then to explore the efficacy of these measures, we consider the utility of policy making from the viewpoints of states, asylum seekers and refugees, and international society. The article concludes with the presentation of four new directions in which policies could move in order better to square the professed interests of Western states with the needs of refugees for protection.
Keywords: F22; J15; H19; O15; 330; asylum; deterrence; welfare; Western states; Asylrecht; Westliche Staaten